Reliability of routine hospital data on poisoning as measures of deliberate self poisoning in adolescents. Issue 4 (December 1990) - Sellar, C; Goldacre, M J; Hawton, K
Abstract : STUDY OBJECTIVE–The aim was to assess the extent to which routinely collected data on poisoning in adolescents reflected deliberate self poisoning and, in doing, so to assess the accuracy of the diagnostic information on poisoning in the routine hospital abstracts which form the joint data base of Hospital Activity Analysis and the Oxford Record Linkage Study (ORLS). DESIGN–A comparison was made (a) of all eligible ORLS records during the study period with an independent source of records; and (b) of a random sample of records from an independent source with ORLS. SETTING–Records of patients admitted to the John Radcliffe Hospital in Oxford were used. SUBJECTS–These were (a) patients aged 10-20 years between 1980 and 1985 with a diagnosis of poisoning by drugs and medicaments in ORLS; (b) a random sample of 500 patients selected from the self harm monitoring files at the hospital (12 patients were not eligible for inclusion in ORLS and were therefore excluded from the rest of the study). MEASUREMENTS AND MAIN RESULTS–The recorded diagnosis was compared on the records selected from the two files. Of the 1123 events of poisoning identified in ORLS, 1081 (96.3%) were correctly coded as poisoning and 1065 (95%) of these were deliberate self poisoning. Of the 488 cases from the monitoring files, 467 (95.7%) of all cases had a correct diagnosis of injury or poisoning on the ORLS file. Of the 453 poisoning cases 436 (96.2%) were correctly recorded in ORLS. CONCLUSIONS–Deliberate self poisoning in adolescents can be identified through routinely collected hospital statistics. A very high percentage of the diagnostic information on poisoning in ORLS files is correctly recorded.